Dampak Reputasi Underwriter,Underpricing Dan Financial Leverage Terhadap Kinerja Initial Public Offering (IPO) - A, Lathif Arafat; Meta, Williya; Meilisa (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to analyze the impact of underwriter reputation, underpricing, and financial leverage on the stock performance of Initial Public Offerings (IPOs) in the Indonesian capital market. Using a quantitative approach, data from companies that conducted IPOs in 2023 were analyzed through multiple linear regression to examine the influence of these three independent variables on IPO performance. The results indicate that both underwriter reputation and financial leverage have a significant impact on long-term IPO stock performance. Reputable underwriters are proven to reduce underpricing and enhance investor confidence. Conversely, underpricing was found to have no significant effect on IPO stock performance. These findings offer valuable insights for companies planning to go public, emphasizing the importance of selecting a reputable underwriter and managing financial leverage to improve stock performance in Indonesia’s capital market. Keywords: Initial Public Offer, Reputasi Underwriter, Underpricing, Financial Leverage